Impact of vaccination against SARS-CoV-2 on mortality risk, ICU admission rate, and hospitalization length in hospitalized COVID-19 patients: a cross-sectional study - Behnam Maleki; Amir M. Sadeghian; Mitra Ranjbar (BMC Infectious Diseases)
Abstract Background Vaccination against SARS-CoV-2 has been crucial in impeding virus spread and preventing fatal complications. Despite growing evidence of vaccine efficacy, data on its impact on hospitalized patients remain limited. We aimed to estimate the risk of mortality, ICU admission, and hospitalization length among hospitalized COVID-19 patients based on vaccination status. Methods In this single-center cross-sectional study, we included patients above 16 years old hospitalized due to COVID-19. Patients were categorized as unvaccinated, partially vaccinated (single dose), or fully vaccinated (at least one booster dose). We performed logistic and linear regression analyses, including both bivariable and multivariable models, to evaluate the association between vaccination status, demographic characteristics, and study outcomes. Results Of 299 participants, 21.7%, 15.7%, and 62.5% were unvaccinated, partially vaccinated, and fully vaccinated, respectively. Full vaccination was associated with significantly reduced mortality risk (OR: 0.235, 95%CI: 0.103–0.538) and lower ICU admission rates (OR: 0.252, 95%CI: 0.131–0.484). Vaccinated patients had shorter hospital stays (fully vaccinated: 6.38 ± 1.65 days; unvaccinated: 9.22 ± 2.84 days, p < 0.001). Older age independently predicted higher mortality (OR: 1.062, 95%CI: 1.030–1.095), ICU admission (OR: 1.047, 95%CI: 1.027–1.068), and longer hospital stays (estimate: 0.027, 95%CI: 0.012–0.043). Multiple comorbidities were associated with higher mortality and longer hospitalization (OR: 1.794, 95%CI: 1.244–2.587; estimate: 0.395, 95%CI: 0.142–0.648). Conclusion Full vaccination against SARS-CoV-2 is associated with significantly improved clinical outcomes in hospitalized COVID-19 patients, including reduced mortality, lower ICU admission rates, and shorter hospital stays.